O25 Using qualitative synthesis data to inform interventions in palliative care: a multilevel approach. (20th March 2019) - Armstrong, Megan; Flemming, Kate; Kupeli, Nuriye; Stone, Patrick; Wilkinson, Susie; Candy, Bridget
Abstract : Introduction: Complex interventions are common in palliative care (PC), but the data from quantitative and qualitative research can be contrasting. For example, systematic reviews found trial evidence on effectiveness was uncertain in complementary therapies (CTs) in PC; however, based on qualitative evidence patients' perceived CT to be highly beneficial for their well-being and highlighted ways in which they wished CT were delivered. Aim: To develop an exemplar in PC that draws together the findings from quantitative and qualitative systematic reviews to inform reasons for discrepancies between the two and suggest directions for future intervention development. Methods: We sought trials on the effectiveness of CT and qualitative studies on patients' perspectives about CTs. Our primary outcomes for trials included anxiety, pain, and quality of life. Eight databases were searched in 2018. Citations and full-text papers were reviewed independently to identify relevant studies. Meta-analyses to pool trial data were considered and a thematic synthesis was conducted to understand patients' experiences as presented in primary qualitative analysis. The individual review findings were combined in matrices to explore similarities and differences. Results: Twenty-two trials and five qualitative studies were included. A matrix table explored the (lack of) overlap between items on a commonly used quality of life measure from the review of trials and the themes from the thematic synthesis. A table was also created to explore the variations between how patients want CT to be delivered and how it is being delivered in trials. Conclusions: This combining of qualitative and quantitative data has highlighted outcome measures in trials may be inappropriate and the interventions may not be delivered how patients wish. Our approach demonstrates a potential way in PC to enhance development of practice appropriate complex interventions.